Her Royal Highness Tengku Ampuan Pahang launches UMPSA Klover Girl Guides Association - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 23 February 2025 – Her Royal Highness Tengku Ampuan Pahang, Tunku Azizah Aminah Maimunah Iskandariah binti Almarhum Sultan Iskandar Al-Haj, who is also the President of the Pahang Branch of the Girl Guides Association, officially launched the UMPSA Klover Girl Guides Association in conjunction with the National-level World Thinking Day (WTD) Celebration. Her Royal Highness officiated the 2025 National-level World Thinking Day (WTD) Celebration at the Sports Complex Hall, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Gambang Campus.